Beneish Model: Detection of Indications of Financial Statement Fraud Using CEO Characteristics - Siti Masruroh; Anita Carolina (Association of Certified Fraud Examiners Indonesia Chapter, 2022)
The study aims to analyze the influence of CEO characteristic factors on indications of financial statement fraud using the Beneish Model. Based on the upper echelon theory, this study proposes six hypotheses which are tested using logistic regression analysis. This study uses secondary data derived from financial statements or annual reports of mining companies listed on the Indonesia Stock Exchange from 2015 to 2019. The results of this study show that CEO characteristics in the form of CEO age, educational background, and work experience cannot be used as indicators that can detect financial statement fraud. Meanwhile, some other characteristics that are still the focus of this study, such asCEO’s gender, tenure, and nationality havean influence on indications of financial statement fraud. So, it can be concluded that the CEO characteristics that have a link in detectingfinancial statement fraud can be considered fraud prevention efforts.